Silla turca vacía e hipopituitarismo. - NECOCHEA, Yngrid; LOJA, David; AVILES, Roberto; VILCA, Maricela (Revista Médica Herediana, 2013)
We present the case of a multiparous and obese woman of 59 years with partial hypopituitarism having an empty sella syndrome. We describe the clinical, radiological and biochemical findings. The diagnosis of empty sella was confirmed by computarized tomography. The levels of thyroxine, cortisol and growth hormone were decreased, with pituitary hyporresponsiveness to hypoglicemia induced with insulin. The replacement therapy was successful.